In Focus/Executive Coaching-Coaching and Performance Substantiating the Link - Weller, Karen; Weller, Karen; Weller, David (Center for Creative Leadership, 2004)
In today's increasingly competitive, fast-paced, and turbulent business environment, organizational success largely depends on having leaders who can articulate a vision, collaborate and communicate effectively, and draw out the full potential of those they lead. It has been estimated that up to 45 percent of an organization's performance is linked to the quality of its executive leadership, so it's clear that effective leaders are key to gaining a competitive edge. One increasingly popular way in which organizations are working to develop better leaders is executive coaching.